Konflik Tokoh Elena Dalam Novel Little Fires Everywhere Karya Celeste Ng - Hopia, Nida (PT. Alahyan Publisher Sukabumi, 2024)
Conflict is an opposition that occurs between individuals or groups, an event can lead to a conflict, as well as a conflict can lead to events as a result. The purpose of this study is to describe the conflict that occurs in the character Elena in the novel Little Fires Everywhere by Celeste Ng. With descriptive qualitative as the research method. In this study the authors chose data collection techniques, including the technique of listening and recording. As for the data analysis technique through three processes, the data reduction process, then the presentation of data and the final stage, namely the conclusion. The results of this study show that the conflicts that occur to Elena's character are divided into internal and external conflicts involving several supporting characters.duals or groups, an event can lead to a conflict, as well as a conflict can lead to events as a result. The purpose of this study is to describe the conflict that occurs in the character Elena in the novel Little Fires Everywhere by Celeste Ng. With descriptive qualitative as the research method. In this study the authors chose data collection techniques, including the technique of listening and recording. As for the data analysis technique through three processes, the data reduction process, then the presentation of data and the final stage, namely the conclusion. The results of this study show that the conflicts that occur to Elena's character are divided into internal and external conflicts involving several supporting characters.